Perception of the risk of living in the mediations of a final disposal site, El Salto, Mexico - Venegas Sahagun, Beatriz Adriana (2023)
[Introduction]: The study of risk perception refers to the reflections and evaluations of people about the dangers to which they, their facilities and their environment are or could be exposed and make decisions about it. [Objective]: This research analyzes the risk perception of the communities Mesa de los Laureles and Fraccionamiento Nueva Vizcaya located in El Salto, Jalisco, Mexico, which are in the vicinity of the Los Laureles Sanitary Landfill. In addition to this, the spatial relationship between the location of people and diseases sensitive to contamination is examined. [Methodology]: A quantitative methodology was used, complemented with Geographic Information Systems, field trips and in-depth interviews. 101 surveys were carried out, the questionnaire was divided into four sections with 21 questions. Descriptive statistics and analysis with simple linear regression and chi-square were performed. [Results]: perceives the changes in their environment, and identifies related diseases, such as gastrointestinal, respiratory, and dermal . Statistical models indicate that illnesses could tentatively be minimized by 2.73% if homes were 2.55 meters further from the landfill. [Conclusions]: the population still perceives the risk from a very limited notion of space, which prevents it from reacting to the threat, likewise it has a portfolio of risks, where living in the vicinity of the landfill is not seen as a significant threat to his physical well-being, and assumes it as an acceptable risk.